[Rezension von: Pioske, Daniel D., 1982-, The Bible among ruins : time, material remains, and the world of the biblical writers] - Burke, Aaron A. (The Biblical archaeology review, 2024)
In recent decades, biblical scholars have begun to explore topics at the intersections of archaeological, biblical, and anthropological studies. Of special interest are questions relating to memory, like Daniel Pioske’s recent The Bible Among Ruins. The book’s relevance is readily apparent to Bible readers familiar with the repeated use of the phrase "to this day," […]